Balansując na krawędzi słowa: specyfika kobiecych świadectw obozowych (Delbo, Millu, Szmaglewska, Żywulska) - Teklik, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
The problem of presenting the traumatic experience of deportation and detention in a concentration camp is still painfully topical, the more so that hitherto existing methods and linguistic strategies provide no useful tools for its investigation, being either frustratingly ineffective, or altogether useless. Over time, a certain regularity in handling the problem has become noticeable, i.e. a distinctive separation of the available accounts of the experience into those provided by women and those evidenced by men. The answer to the question of how to narrate has to be then preceded by an appropriate question on social, cultural and gender identity of the narrator. On the basis of the exemplary accounts by four former inmates of the concentration camp at Auschwitz-Birkenau it is possible to understand the specificity and uniqueness of feminine perception of the camp’s reality. The accounts provided by Charlotte Delbo, Liana Millu, Seweryna Szmaglewska and Krystyna Żywulska — all easily identifiable by the different adopted form of message conveyance — share the specificity of women’s subjects raised, aspects closely related to the structure of a woman and her existence in responding to extreme conditions, often omitted in accounts provided by male witnesses. Camp pregnancies, dramatic deliveries, pseudo-scientific experiments, rapes and prostitution — all these constitute additional themes related to by women, victims to the above.